Formation of S0s in extreme environments III: the role of environment in the formation pathways. Issue 1 (25th June 2022) - Coccato, Lodovico; Fraser-McKelvie, Amelia; Jaffé, Yara L; Johnston, Evelyn J; Cortesi, Arianna; Pallero, Diego
ABSTRACT: It is well established that there are at least two main channels to form lenticular (or S0) galaxies. The first, which we name 'faded spiral' scenario, includes quenching events that led to consumption or removal of gas from a spiral progenitor. The second, which we call 'merger' scenario, includes merger-like events and interactions between galaxies. Each scenario leaves characteristic signatures in the newly formed lenticular galaxy. However, the conditions that trigger one mechanism over another are still unknown. This paper is the third of a series aimed at understanding the role of the environment in the formation of lenticular galaxies. In this study, we combine the kinematics, morphology, and properties of the stellar populations of 329 S0s from the SAMI and MaNGA surveys in order to highlight the role of the environment in the process. We divide the S0s into two classes (A and B) according to their global properties, that we can associate to the products of a faded spiral scenario (class A) or a merger scenario (class B). We then study how the various classes are distributed within different environments. Our study reveals that the 'faded spiral' pathway is the most efficient channel to produce S0s, and it becomes more efficient as the mass of the group or cluster or local density of galaxies increase. The merger pathway is also a viable channel, and its efficiency becomes higher with decreasing local density or environment mass.